Maritime activity and risk patterns in the High North : MARPART Project Report 2 - Borch, Odd Jarl; Andreassen, Natalia; Marchenko, Nataliya A.; Ingimundarson, Valur; Gunnarsdóttir, Halla; Jakobsen, Uffe; Kern, Bolette; Iudin, Iurii; Petrov, Sergey; Markov, Sergey; Kuznetsova, Svetlana (Nord universitet, 2016)
This report provides a discussion on dominating risk factors, risk types and probability of unwanted incidents in the Arctic region. It also provides a coarse-grained evaluation of the potential consequences of different incidents in the northern sea areas of Russia, Norway, Greenland, and Iceland. The risk assessment build upon statistics on vessel activity, case studies of real incidents, and expert evaluation of defined situations of hazard and accident (DSHA). The evaluations of this study may serve as a platform for more detailed assessments, and as input for discussions on priority areas in respect to safety measures and emergency preparedness. In the Marpart Project, the risk assessments have a special role as input into the analyses of emergency management capabilities, and the need for special government efforts in cross-border cooperation.